C5L2 CRISPR KO enhances dental pulp stem cell-mediated dentinogenesis via TrkB under TNFα-induced inflammation - Irfan, Muhammad; Marzban, Hassan; Chung, Seung (Frontiers in Cell and Developmental Biology, 2024)
Dental caries is one of the most common human pathological conditions resulting from the invasion of bacteria into the dentin. Current treatment options are limited. In many cases, the endodontic therapy leads to permanent pulp tissue loss. Dentin-pulp complex regeneration involves dental pulp stem cells (DPSCs) that differentiate into odontoblast-like cells under an inflammatory context. However, limited information is available on how DPSC differentiation processes are affected under inflammatory environments. We have identified the crucial role of complement C5a and its receptor C5aR in the inflammation induced odontoblastic DPSC differentiation. Here, we further investigated the role of a second and controversial C5a receptor, C5L2 in this process and explored the underlying mechanism. Human DPSCs were examined during 7, 10, and 14-day odontogenic differentiation treated with TNFα, C5L2 CRISPR, and tyrosine receptor kinase B (TrkB) antagonist (Cyclotraxin B; CTX-B). Our data demonstrate that C5L2 CRISPR Knock-out (KO) enhances mineralization in TNFα-stimulated differentiating DPSCs. We further confirmed that C5L2 CRISPR KO significantly enhances dentin sialophosphoprotein (DSPP) and dentin matrix protein-1 (DMP-1) expression after 14-day odontoblastic DPSC differentiation and treatment with CTX-B abolished the TNFα/C5L2 CRISPR KO-induced DSPP and DMP-1 increase suggesting the TrkB`s critical role in this process. Our data suggest a regulatory role of C5L2 and TrkB in the TNFα-induced odontogenic DPSCs differentiation. This study may provide a useful tool to understand the mechanisms of the role of inflammation in dentinogenesis that is required for successful DPSC engineering strategies.